An Artificial Electrode/Electrolyte Interface for CO2 Electroreduction by Cation Surfactant Self‐Assembly. (31st August 2020) - Zhong, Yang; Xu, Yan; Ma, Jun; Wang, Cheng; Sheng, Siyu; Cheng, Congtian; Li, Mengxuan; Han, Lu; Zhou, Linlin; Cai, Zhao; Kuang, Yun; Liang, Zheng; et al.
Abstract: In this work, an artificial electrode/electrolyte (E/E) interface, made by coating the electrode surface with a quaternary ammonium cation (R4 N + ) surfactant, was successfully developed, leading to a change in the CO2 reduction reaction (CO2 RR) pathway. This artificial E/E interface, with high CO2 permeability, promotes CO2 transportation and hydrogenation, as well as suppresses the hydrogen evolution reaction (HER). Linear and branched surfactants facilitated formic acid and CO production, respectively. Molecular dynamics simulations show that the artificial interface provided a facile CO2 diffusion pathway. Moreover, density‐functional theory (DFT) calculations revealed the stabilization of the key intermediate, OCHO*, through interactions with R4 N + . This strategy might also be applicable to other electrocatalytic reactions where gas consumption is involved. Abstract : An artificial quaternary ammonium cation (R4 N + ) surfactant electrode/electrolyte (E/E) interface construction strategy changes the CO2 reduction reaction (CO2 RR) pathway. Molecular dynamics simulations indicate that the artificial interface provided a facile CO2 diffusion pathway. DFT calculations revealed the stabilization of the key intermediates through interactions with R4 N + .